Penerapan Teknologi Atap Skylight pada Bentuk Atap Pelana Bangunan di Depok, Indonesia - Dyah Nurwidyaningrum; Tri Wulan Sari; Linda Sari Wulandari; Ega Edistria; Darul Nurjanah; Rita Farida; Eri Ester Khairas; Siti Aisyah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2024)
The purpose of this community service is to implement a skylight roof on the main Biman Foundation building and increase the natural lighting entering the room from the initial 100 lux to 300 lux. The activity began by conducting a survey of the building to discuss permits and manufacturing location. Next, design preparation and RAB calculations for the skylight roof are carried out, followed by making a 3-dimensional DED (Detail Engineering Design) drawing. Then, cost calculations and material surveys are carried out in accordance with the budget and design specifications. Then, coordination was carried out with the Biman Foundation in determining the implementation time, all preparations, such as purchasing and placing materials at the location, as well as registering local residents who were willing to participate in the implementation of the skylight roof renovation. The results obtained can be installed with a skylight roof. The benefit to the foundation is that the natural lighting entering the room increases from the initial 100 lux to 300 lux. So, you can save electricity usage during the day.